2013
DOI: 10.1089/hum.2013.153
|View full text |Cite
|
Sign up to set email alerts
|

Human Cone Visual Pigment Deletions Spare Sufficient Photoreceptors to Warrant Gene Therapy

Abstract: Human X-linked blue-cone monochromacy (BCM), a disabling congenital visual disorder of cone photoreceptors, is a candidate disease for gene augmentation therapy. BCM is caused by either mutations in the red (OPN1LW) and green (OPN1MW) cone photoreceptor opsin gene array or large deletions encompassing portions of the gene array and upstream regulatory sequences that would predict a lack of red or green opsin expression. The fate of opsin-deficient cone cells is unknown. We know that rod opsin null mutant mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 63 publications
(87 reference statements)
2
106
0
Order By: Relevance
“…Dashed lines indicate region of uncertainty defined as translation of the normal variability along the idealized model of a pure photoreceptor degeneration. Results in patients with BBS1 (n ¼ 6), USH2A (n ¼ 7) and RPGR (n ¼ 16) mutations [modified from (21,24,46,47); Supplementary Table S1] are shown with gray symbols; the values fall inside predicted limits of the model. LCA patients with NPHP5 and CEP290 mutations (red and pink triangles) show better structure than predicted by the model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dashed lines indicate region of uncertainty defined as translation of the normal variability along the idealized model of a pure photoreceptor degeneration. Results in patients with BBS1 (n ¼ 6), USH2A (n ¼ 7) and RPGR (n ¼ 16) mutations [modified from (21,24,46,47); Supplementary Table S1] are shown with gray symbols; the values fall inside predicted limits of the model. LCA patients with NPHP5 and CEP290 mutations (red and pink triangles) show better structure than predicted by the model.…”
Section: Resultsmentioning
confidence: 99%
“…Overlapping, non-averaged, 9 mm-length scans through the fovea were used to study the retina, and were analyzed with custom programs (MatLab 7.5; MathWorks, Natick, MA). For the outer retinal sublaminae, signal peak assignments were based on our previously published work (21,24,46,47). Foveal ONL and distal substructure thicknesses were measured from three OCT scans through the fovea obtained at the same visit in the NPHP5-LCA patients, and compared with measurements in groups of patients with four other genotypes.…”
Section: Optical Coherence Tomography (Oct) Imaging and Analysesmentioning
confidence: 99%
“…Blue cone monochromats have no functioning L-or M cones, and must rely entirely on S cones for photopic vision; as a consequence, they have low vision and no color vision. Deletions of the locus control region impairs function of cone photoreceptors, but adaptive optics imaging suggests that at least some fraction of L/M cones remain viable and amenable to gene therapy (Carroll et al 2012;Cideciyan et al 2013). Likewise, for the cone opsin mutation designated LIAVA (for the combination of amino acids specified by five polymorphic codons in exon 3), the cones are rendered nonfunctional but they do not appear to degenerate .…”
Section: Means Of Delivery For Gene Therapy: Subretinal Versus Intravmentioning
confidence: 99%
“…[10,11] While all mutations resulted in reduced retinal thickness and disruption of the photoreceptor mosaic, there were distinct patterns in the distribution and extent of the disruption between genotypes. Those with predominantly stable phenotypes (LCR deletions and p.Cys203Arg) had largely preserved lamination of the retina with disruption confined to a focal section only of the inner segment (Ise) layer, which corresponded to the S cone free zone of the fovea.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Recent studies have shown that cone opsin disorders, with specific visual and retinal phenotypes, are caused by several different genetic mechanisms. [10][11][12] As a result, genotype-phenotype correlations are beginning to emerge that influence predictions of the course and severity of disease. …”
mentioning
confidence: 99%